Preparation and Antibacterial Activity of Some New 4-(2-Heterylidenehydrazinyl)-7-chloroquinoline Derivatives - Trong Duc Le; Ngoc Nam Pham; Tien Cong Nguyen (Journal of Chemistry)
N-(4-Substituted phenyl)acetamides, which were prepared from acetic anhydride and p-substituted anilines, were utilized as precursors for reactions to Vilsmeier-Haack reagent to form 6-substituted-2-chloroquinoline-3-carbaldehydes 3a–c. Meanwhile, a similar reagent was applied to 1-[1-(4-substituted phenyl)ethylidene]-2-phenylhydrazines as substrates, which were synthesized from phenylhydrazine hydrochloride and p-substituted acetophenones, and 1,3-diarylpyrazole-4-carbaldehydes 3d–f were observed as a result. Reactions between the aldehydes 3a–f and 7-chloro-4-hydrazinylquinoline 2, obtained from reaction of 4,7-dichloroquinoline 1 and hydrazine hydrate, formed six new hydrazone compounds, namely, 4-{2-[(6-substituted-2-chloroquinolin-3-yl)methylidene]hydrazinyl}-7-chloroquinolines 4a–c and 4-(2-{[3-(4-substituted phenyl)-1-phenyl-1H-pyrazol-4-yl]methylene}hydrazinyl)-7-chloroquinolines 4d–f. The chemical structures of all synthesized compounds were elucidated by the analysis of IR, 1H, 13C-NMR, and HRMS spectral data. Additionally, all of the synthesized hydrazones were evaluated in terms of cytotoxic activity against four strains of bacteria and four strains of fungus at several concentrations of substrates. As a result, three of them, 4a–c, possess the good ability as growth inhibitor of Bacillus subtilis and Aspergillus niger at the concentration of 25 μg/mL and 50 μg/mL, respectively, while compound 4e only shows a cytotoxic activity against Aspergillus niger at the concentration of 25 μg/mL.